DETERMINAN STATUS GIZI REMAJA PUTRI DI MAN MODEL BUKITTINGGI TAHUN 2008 - Nini Rahmi; Azrimaidaliza Azrimaidaliza; Edmon Edmon (Jurnal Kesehatan Masyarakat Andalas, 2009)
The female adolescents are the future generation of the country and they are expected to birth a quality and healthy generation in the next day, for that need a good nutrient. According to the result of preliminary study, 23% of the female adolescents had malnutrition by Body Mass Index (BMI), and they have not got enough attention in the effort of preventing and eliminating the case of malnutrition. Consumption of macro nutrient, physical activity, body image, nutrient knowledge and attitude are factors that related to nutritional status. The objective of this research was to obtain illustration about female adolescent nutritional status and factors that related to it. The research design was Cross Sectional Study that was done in December 2007 — June 2008. The sample of this research was 65 girl students, taken by proportional. The nutritional status was determined by BMI, was taken from height and weight of each respondent. Nutritional consumption (energy, protein, fat and carbohydrate) collected by 24 hours recall. Then physical activity, body image, nutrient knowledge and attitude of respondent were collected by questionnaire. The data were analyzed with Chi-Square test to observe the relationship between the variables. The result showed that 21.5% of the female adolescents were malnutrition, 56% respondents got the low energy consumption, 33,8% low protein consumption. 16,9% low fat consumption and 53,8% low carbohydrate consumption, 52,3% had high physical activity, 5Q,8%> had negative body image, 55,4% had low nutrient knowledge and 24,6%> had negative attitude. The analyze showed that there was a significant relation between protein consumption, fat consumption, physical activity and body image with nutrient status respondent (p<0,05). It suggested the Health Department of Bukittinggi should do the trainingfor health workers and teachers continuity minimal once a year. They should explain nutrition information and promotion for female adolescents and notice the students nutrient status periodically. It also suggests to improve the activities of Health School Organization (UKS) and health adolescent cadre for using optima! Health Card Student.